Relationship Between the Practice of Consuming Pork Lawar and the Prevalence of Taeniasis in Kerobokan Village, Badung Regency, Bali - Ni Luh Putu Ayu Gayatri; Hemma Yulfi (Talenta Publisher, 2023)
Background: Taeniasis is an infection brought on by Taenia sp. Tapeworms, one of which is Taenia solium, whose intermediate host is swine. Adult tapeworms develop in the intestines of the host (human) after consuming infected pork that was not properly prepared. Objective: To determine the relationship between the consumption of pork lawar and the incidence of taeniasis in the village of Kerobokan, Badung Regency, Bali. Methods: This is a correlative categorical research with a cross sectional design. The study population is people in Kerobokan Village, Bali Province. Using power of 0.8 strength of linear correlation of 0.25, and additional 10% for incomplete data, we obtain sample size of 128 people who meet inclusion criteria. Data was obtained by filling out a set of validated questionnaire. Results: Sixty-five out of 128 respondents (50.8%) were found to possess a positive inclination towards the consumption of pork lawar, and only 1 (one) respondent (0.08%) had a history of taeniasis. The significance value of the correlation (p) between the habit of eating pork lawar and a history of taeniasis was 0.312. Conclusion: There is a lack of correlation between the practise of consuming pork lawar and the prevalence of taeniasis among the population.